Synthesis And Characterization Of Silver Nanoparticles Using Gandaria (Bouea macrophylla Griff.) Seed Extract As Bioreductor And Ouw Natural Clay (ONC) As Matrix - Kiat, Jaleha; Bijang, Catherina M; Sutapa, Wayan; Sekewael, Serly J (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
The synthesis of silver nanoparticles (AgNP) was achieved by utilizing gandaria seed extract as a bioreductant and Ouw natural clay (ONC) as a matrix. An investigation was conducted on the volume of a silver nitrate solution with a concentration of 1 x 10-3 M, which served as a precursor. The silver nanoparticles were analyzed using UV-Vis spectroscopy to assess their surface plasmon resonance (SPR) and stability. The results indicate that the SPR of silver nanoparticles occurs at a wavelength range of 432-450 nm. X-ray diffraction (XRD) was also employed for characterization purposes to ascertain the existence of silver nanoparticles that were generated within the ONC matrix. The XRD characterization data indicate that the Ag/ONC nanocomposite achieved the maximum stability and nanoparticle content when a volume of 500 mL of AgNO3 0.1 M (S5) was added. The mean crystal size of the silver nanoparticles generated is 48.48 nm, with a crystal orientation of both BCC (Body-Centered Cubic) and FCC (Face-Centered Cubic).